Fenomena Peningkatan Permohonan Isbat Nikah di Pengadilan Agama Sibuhuan Tahun 2020-2021 - Marwah Amelia Sari Harahap; Imam Yazid (Universitas Medan Area, 2023)
Couples who cannot prove their marriage with a marriage certificate can submit a marriage certificate application to the Religious Court. This study aims to determine the factors causing the increase in applications for marriage certificates in the Sibuhuan Religious Court. The problem is focused on increasing applications for marriage certificates at the Sibuhuan Religious Court for 2020-2021. The data were collected through a field approach and literature were analyzed qualitatively using a Juridstic Empirical type of research. It was found that in the practice of carrying out marriages there are still many people who do not have a marriage certificate due to negligence in recording marriages. Then, with the increase in public legal awareness regarding the ownership of marriage certificates so that people are very enthusiastic about legalizing their marriages which were not originally recorded in countries with marriage certificates. There is an integrated marriage registration program with an easy submission process, fast completion, low cost and even free for the less fortunate. The facts that have been mentioned are the factors causing the increase in applications for marriage certificates in 2020-2021 at the Sibuhuan Religious Court.